Host-tourist interaction and impact of tourism on residents’ Quality of Life - Maria João Carneiro; Celeste Eusébio (Tourism & Management Studies)
This paper analyses the relationship between host-tourist interactions and residents’ perceptions of tourism impacts on their QOL. A survey of residents in two Portuguese beach communities was conducted. Two PCAs were used to identify dimensions of host-tourist interaction and QOL domains. Furthermore, an importance-perceived impact analysis and Paired t-tests were carried out to identify gaps between the levels of importance that residents attribute to several domains of their QOL and their perceptions of tourism impacts in these QOL domains. Correlation tests were used to find statistical significant associations between host-tourist interaction dimensions and residents’ QOL domains. Results suggest that the interaction between residents and visitors in these destinations is low and very superficial, gaps between importance and tourism impacts emerged in several domains of residents’ QOL and there is a positive relationship between host– tourist interactions and residents’ perceptions of tourism impacts on several domains of their QOL. Th